2015
DOI: 10.1007/s00464-015-4416-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of combined endoscopic/laparoscopic intragastric enucleation of presumed gastric stromal tumors

Abstract: Enucleation of intact gastrointestinal stromal tumors can be accomplished with low risk of recurrence when done with a combined endoscopic/laparoscopic intraluminal technique. It should be the preferred approach considered for small, proximal, intraluminal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…[ 2 ] However, smaller tumors (<20–30 mm) can be safely considered for endoscopic resection, with or without laparoscopic control. [ 20 21 ] Consequently, NCCN guidelines recommend follow-up only in tumors <20 mm without high-risk EUS features while the rest should be resected. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] However, smaller tumors (<20–30 mm) can be safely considered for endoscopic resection, with or without laparoscopic control. [ 20 21 ] Consequently, NCCN guidelines recommend follow-up only in tumors <20 mm without high-risk EUS features while the rest should be resected. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…The resected specimen is placed in a plastic bag (Rusch MemoBag; Teleflex, Tokyo, Japan) and removed intraluminally using endoscopy if the size of the tumor is ≤ 5 cm[ 20 , 80 ]. Larger tumors of > 5 cm are removed trough the umbilicus with a plastic bag.…”
Section: Oral Approach By Endoscopic Visualizationmentioning
confidence: 99%
“…Moreover, it is often difficult to extract the purified data of only PEIGS cases, while they contain mixed operative methods and results of unclassified groups. Mino et al (29) reported the long-term outcomes of 15 cases, who were followed up for max. 61 months and presented no recurrence.…”
Section: Oncological Outcomesmentioning
confidence: 99%